An ultra-sensitive bionic skin sensor with strain visualization
By combining the microconvex photonic crystal layer and composite conductive film in the sensor, the problem of the existing sensors being disconnected under the small strain detection sensitivity and high strain range is solved, and the strain detection of ultra-high sensitivity and wide sensing range is achieved.
Patent Information
- Application Number
- CN202410274848.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-11
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-03-11
AI Technical Summary
Existing elastic strain sensors are insufficient in detecting tiny strains, and they are prone to disconnect the conductive path under high strain ranges, limiting their application range.
A super sensitive bionic skin sensor for strain visualization was designed, using the microconvex photonic crystal layer in the upper elastic matrix and the composite conductive film in the lower elastic matrix to achieve visualization and high sensitivity detection of strain through structural color changes and resistance changes.
It realizes structural color display with ultra-high sensitivity, wide sensing range, high stability and high brightness, and can accurately monitor strain signals in complex environments and is suitable for detection of multiple strain ranges.
Smart Images

Figure CN118392024B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nanocomposite materials, and in particular to an ultra-sensitive bionic skin sensor with strain visualization. Background Art
[0002] As the demand for real-time monitoring and high-precision data in the medical field continues to increase, elastic strain sensors are developing rapidly in the medical field. Elastic strain sensors made of elastic materials integrated with wearable technology can be flexibly attached to human skin and joints to perform high-precision real-time monitoring of human physiological and motion signals. Common transmission methods of elastic strain sensors include electrical signals, optical signals, and magnetic signals.
[0003] Common electrical signal strain sensors encode the perceived external physical and mechanical stimuli into detectable electrical signals, but a single electrical output is difficult to cope with complex outdoor emergencies. The optoelectronic dual-function strain sensor obtained by integrating the structural color strain sensor can realize direct intelligent interaction between the device and the user, while making up for the detection defects of the structural color strain sensor in small strains. The subtle physiological movement signals of the human body are accurately monitored through the conductive network, and the large strain joint movement can be visually read out through the optical signal while the electrical signal is monitored. In an emergency, the degree of human impact can be quickly judged, providing important reference information for doctors.
[0004] At present, there have been some studies on this type of sensor, but there are still many problems. For example, the most common type of existing optoelectronic dual-function strain sensor is the conductive photon gel type, that is, filling the photon gel with conductive materials or conductive polymers. For example, Chinese patent CN111393708A provides a stretchable adhesive conductive structural color hydrogel film and its preparation method, and the hydrogel solution is cast in the inverse opal structure. However, since the color brightness of the structural color depends on the refractive index contrast of the material, and the refractive index of the hydrogel is slightly different from that of the photonic crystal material, it is difficult to show a color with higher brightness. In addition, the sensitivity of the dual-function strain sensor based on structural color and resistance is usually limited by materials and design. In the low strain range, the electrical signal sensitivity of the sensor is low (GF<5), and it is impossible to accurately measure small strain changes. In addition, this type of device is suitable for measuring small to medium strain changes. When it is necessary to measure a very large strain range or an ultra-large strain (ε>50%), it is easy to cause the conductive path to be disconnected, thereby limiting the application range of the device.
[0005] Elastic strain sensors made of nanomaterials have the advantages of high sensitivity, rapid response, and stretchability. However, in the device preparation process, due to the special properties and structure of nanomaterials, it is very challenging to ensure that the nanomaterials are closely combined with other components to maintain the stability of the device. Based on this, the present invention provides an ultra-sensitive bionic skin sensor with strain visualization. Summary of the invention
[0006] The purpose of the present invention is to provide an ultra-sensitive bionic skin sensor with strain visualization, which makes up for the deficiency of existing elastic strain sensors that can only transmit a single electrical signal, and at the same time has the advantages of high structural color brightness, ultra-sensitivity, wide sensing range and high stability.
[0007] In order to achieve the above-mentioned purpose, the present invention provides the following technical solutions: an ultra-sensitive bionic skin sensor with strain visualization, comprising an upper elastic matrix, a micro-convex photonic crystal layer arranged on the upper elastic matrix, a lower elastic matrix and a composite conductive film arranged in the lower elastic matrix. The photonic crystal layer is used to simulate the chameleon skin to judge the degree of strain through structural color changes to achieve visualized sensing. The photonic crystal layer enhances two-dimensional Bragg diffraction, significantly enhances the vividness of structural color, and has dual-function sensing.
[0008] Preferably, the photonic crystal is formed by a periodic arrangement of nanoparticles, and the micro-convex photonic crystal layer refers to an array of nanoparticles embedded in an upper elastic matrix that is partially exposed on the surface to form a periodic convex structure.
[0009] Preferably, the micro-convex photonic crystal layer produces a high refractive index contrast with the air, and under tensile strain, a sinusoidal submicron structure is formed due to the mismatch between the nanoparticles and the elastic matrix modulus, which acts as a diffraction grating to enhance the two-dimensional Bragg diffraction. The simultaneous action of the two significantly improves the vividness of the structural color.
[0010] The composite conductive film is used to simulate the slit sensors on the legs of a bionic spider and the elastic fibers of human skin, and can achieve ultra-sensitive and highly stable sensing by judging the degree of tiny strains through changes in resistance.
[0011] Preferably, the composite conductive film includes a conductive layer, a connecting layer and a sensitizing layer. The sensitizing layer in the composite conductive film is used to mimic the slit sensor on the legs of a spider to achieve ultra-high sensitivity. The connecting layer is used to enhance the interfacial adhesion and improve the stability and reliability of the conductive network. The conductive layer is used to mimic the elastic fibers in human skin to achieve high stretchability.
[0012] Preferably, when the sensor is subjected to a slight deformation, micron-sized cracks will appear in the conductive layer of the composite conductive film, causing a sharp change in resistance, thereby achieving ultra-high sensitivity; when the sensor is subjected to a larger deformation, the cracks will further expand, and the connecting layer will dominate the connection of the conductive path, allowing the sensor to achieve high elasticity and high elongation while maintaining conductivity.
[0013] Preferably, the conductive layer is composed of a one-dimensional nanomaterial, the connecting layer is composed of a viscous coating, and the sensitizing layer is composed of a brittle two-dimensional conductive material; the one-dimensional nanomaterial is selected from any one of AgNWs, AuNWs, and carbon nanotubes; the viscous coating is selected from any one of polyvinyl alcohol, polyvinylamine, and polydopamine, and the brittle two-dimensional conductive material is selected from any one of MXene, graphene, and molybdenum disulfide.
[0014] Preferably, the sensor has an electrical signal detection range of 0-80%, an electrical signal sensing sensitivity GF>10, an optical signal detection range of -30-300%, and an optical signal sensing sensitivity>0.5nm / %.
[0015] The present invention also includes a method for preparing an ultra-sensitive bionic skin sensor with strain visualization, comprising the following steps:
[0016] S01. Preparation of photonic crystal layer: uniformly dispersing photonic crystal colloidal solution on the surface of deionized water to form two-dimensional photonic crystal; forming a close-packed structure of the two-dimensional photonic crystal through the surface tension ladder effect; transferring to a hydrophilic glass slide and adjusting the gap between colloidal nanoparticles to obtain a non-close-packed structure; adding a polymer solution and curing it, then peeling it off from the glass slide. Since the elastic matrix after curing is still sticky, a part of it will remain on the glass slide during peeling, thus obtaining a photonic crystal layer with a micro-convex structure;
[0017] S02. Preparation of composite conductive film: vacuum filter the one-dimensional nano conductive solution and obtain a conductive film after drying; drip the polymer solution and solidify it before peeling it off; modify the surface of the conductive film to improve the connectivity between the conductive networks; drip and dry the two-dimensional conductive solution; drip the polymer solution and solidify it for encapsulation;
[0018] S03. Embed the two-dimensional photonic crystal in the upper elastic matrix and semi-embed the composite conductive film in the lower elastic matrix to obtain an ultra-sensitive bionic skin sensor with strain visualization.
[0019] The strain-visualized ultra-sensitive bionic skin sensor prepared by the present invention is applied to any one or more fields of wearable electronic products, medical equipment, and intelligent robots.
[0020] In the above technical solution, the technical effects and advantages provided by the present invention are:
[0021] 1. The present invention provides an ultra-sensitive bionic skin sensor with strain visualization, specifically a bionic skin sensor with ultra-high sensitivity, wide sensing range and high stability, the structure of which includes an upper elastic matrix, a micro-convex photonic crystal layer arranged on the upper elastic matrix, a lower elastic matrix and a composite conductive film arranged in the lower elastic matrix; wherein the nanoparticles in the photonic crystal layer are pre-processed to widen the optical signal sensing range, and the composite conductive film provides ultra-high sensitivity and high stability;
[0022] 2. The present invention forms a micro-convex structure by embedding a non-tightly arranged photonic crystal layer into an upper elastic matrix. The refractive index of the elastic matrix is generally 1.4-1.6, the refractive index of commonly used nanoparticles (PS, SiO2) is generally 1.4-1.6, and the refractive index of air is 1. Therefore, the photonic crystals with a micro-convex structure will produce a high refractive index contrast with the air. And under tensile strain, due to the mismatch between the modulus of the hard nanoparticles and the elastic matrix, a sinusoidal submicron structure will be formed, which acts as a diffraction grating to enhance the two-dimensional Bragg diffraction and significantly improve the vividness of the structural color;
[0023] 3. The present invention embeds the conductive layer in the composite conductive film into the lower elastic matrix, so that the conductive material can form a stable current conduction path in the matrix, thereby improving the mechanical stability and durability of the sensor, and at the same time enhancing the conductive material's ability to perceive strain, thereby more accurately monitoring the strain signals in complex environments;
[0024] 4. The present invention performs hydrophilic treatment and viscosity treatment on the conductive layer in the composite conductive film to improve the adhesion of the sensitizing material on the conductive material, reduce the shedding of the sensitizing material under large strain, and improve the stability and reliability of the conductive network;
[0025] 5. The sensitization layer in the composite conductive film of the present invention is selected from brittle two-dimensional conductive materials. Such materials have a high Poisson's ratio. Larger deformations in the vertical direction can produce larger resistance changes, and can produce obvious electrical signal responses even under small strains.
[0026] 6. The sensitization layer in the composite conductive film of the present invention has a black background and light-absorbing properties, and can absorb light scattered and reflected at other wavelengths, making the optical signal present a brighter structural color. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a schematic diagram of the structure of the ultra-sensitive bionic skin sensor with strain visualization of the present invention;
[0028] Figure 2 A diagram showing the preparation process of the photonic crystal layer in the ultra-sensitive bionic skin sensor with strain visualization of the present invention;
[0029] Figure 3This is a diagram of the preparation process of the composite conductive film in the ultra-sensitive bionic skin sensor with strain visualization of the present invention;
[0030] Figure 4 This is a comparison diagram of the photonic crystal layer on the black conductive background and the photonic crystal layer on the glass slide of the present invention, a is the glass slide background, b is the black conductive background;
[0031] Figure 5 The SEM images of the colloidal nanoparticles before and after the spacing treatment in the preparation process of the embodiment of the present invention are compared, a is before the spacing treatment, and b is after the spacing etching for 5 minutes;
[0032] Figure 6 The photonic crystal layer with a micro-convex structure prepared in an embodiment of the present invention, a is a preparation process diagram, and b is a SEM diagram;
[0033] Figure 7 Comparison of packaged and embedded photonic crystal layers. a is a digital image of structural colors at different angles, and b is a digital image of structural colors under 50% tensile strain.
[0034] Figure 8 The schematic diagram of the packaged and embedded photonic crystal layer and the mechanical simulation diagram under 50% strain, a is the schematic diagram, b is the mechanical simulation diagram;
[0035] Fig. 9 This is a SEM image of the composite conductive film during the preparation process of an embodiment of the present invention;
[0036] Fig.10 A diagram of the electrical signal sensing mechanism of the ultra-sensitive bionic skin sensor with strain visualization prepared in accordance with an embodiment of the present invention;
[0037] Fig.11 A graph showing changes in the reflection peak position during the stretching and releasing cycles of an ultra-sensitive bionic skin sensor with strain visualization prepared for an embodiment of the present invention;
[0038] Fig.12 A relative resistance change curve diagram of an ultra-sensitive bionic skin sensor with strain visualization under different strains prepared in an embodiment of the present invention;
[0039] Fig.13 It is a graph showing the relative change of peak value and the change of peak value average value under the stretching-releasing cycle of Comparative Example 1 and Example 1 of the present invention;
[0040] Fig.14 This is a comparison diagram of the relative resistance changes of Comparative Example 2 and Example 1 of the present invention under increasing strain;
[0041] Fig.15 This is a diagram showing the structural color changes of the ultra-sensitive bionic skin sensor with strain visualization under different tensile stresses produced in an embodiment of the present invention;
[0042] Fig.16 A graph of electrical signal changes during stretching and releasing cycles of an ultra-sensitive bionic skin sensor with strain visualization prepared for an embodiment of the present invention;
[0043] Fig.17 Figure 1 is a graph showing the sensing results of the human physiological motion signal according to the embodiment of the present invention. Figure a is a relative resistance change curve of the pulse, Figure b is a relative resistance change curve when swallowing, Figure c is a relative resistance change curve of breathing, and Figure d is a relative resistance change curve of facial expression.
[0044] Description of reference numerals:
[0045] 1 upper elastic matrix, 2 photonic crystal layer, 3 lower elastic matrix, 4 composite conductive film, 41 conducting layer, 42 connecting layer, 43 sensitization layer. DETAILED DESCRIPTION
[0046] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention will be further described in detail below with reference to the accompanying drawings.
[0047] The present invention provides Figure 1-12 The structure of the ultra-sensitive bionic skin sensor with strain visualization shown in the figure specifically includes an upper elastic matrix 1, a photonic crystal layer 2 arranged in the upper elastic matrix 1, a lower elastic matrix 3 and a composite conductive film 4 arranged in the lower elastic matrix 3;
[0048] The photonic crystal layer 2 is used to simulate the chameleon skin to judge the degree of strain through structural color changes to achieve visual sensing, and the composite conductive film 4 is used to simulate the slit sensors on the legs of spiders and the elastic fibers of human skin to judge the degree of tiny strain through resistance changes to achieve ultra-sensitive and highly stable sensing;
[0049] The photonic crystal is formed by the periodic arrangement of nanoparticles. The micro-convex photonic crystal layer (referring to the nanoparticle array embedded in the upper elastic matrix 1) is partially exposed on the surface to form a periodic convex structure. The micro-convex photonic crystal layer 2 produces a high refractive index contrast with the air, and under tensile strain, a sinusoidal submicron structure is formed due to the mismatch between the modulus of the nanoparticles and the elastic matrix. As a diffraction grating, it enhances the two-dimensional Bragg diffraction. The simultaneous action of the two significantly improves the brightness of the structural color.
[0050] The upper layer of the composite conductive film 4 is a conducting layer 41 , the middle layer is a connecting layer 42 , and the lower layer is a sensitization layer 43 .
[0051] The present invention also provides a method for preparing the above-mentioned ultra-sensitive bionic skin sensor with strain visualization, and the preparation process is as follows:
[0052] S01. Preparation of photonic crystal layer 2, such as Figure 2As shown:
[0053] S011. The colloidal nanoparticle solution dispersed in anhydrous ethanol is uniformly dispersed on the surface of deionized water;
[0054] The colloidal nanoparticles can be selected from polystyrene nanoparticles, silicon dioxide nanoparticles, copper oxide nanoparticles, and zinc oxide nanoparticles, preferably polystyrene nanoparticles, the diameter of which is 100-1000 nm, preferably 500 nm, and the concentration of the colloidal nanoparticle solution dispersed in anhydrous ethanol is 2%;
[0055] S012. Add 10-1000μl of surfactant, preferably 500μl, to the surface of deionized water;
[0056] The surfactant can be selected from sodium dodecyl sulfate (SDS), sodium alkyl ether sulfate (AES), sodium lauryl polyoxyethylene ether sulfate (SLES), preferably SDS;
[0057] S013. Take a clean glass slide and perform hydrophilic treatment, and remove the densely packed two-dimensional photonic crystal assembled on the water surface;
[0058] The hydrophilic treatment can be selected from piranha solution treatment and plasma treatment, preferably plasma treatment, and the plasma treatment conditions are: time (30-100) s, power (60-70) W, and gas atmosphere is oxygen;
[0059] S014. Etching the close-packed two-dimensional photonic crystal obtained in step S013 to obtain a non-close-packed two-dimensional photonic crystal;
[0060] The etching method can be selected from solvent etching, plasma etching, electrochemical etching, and light-assisted etching, preferably plasma etching, and the plasma treatment conditions are: time (120-300) s, power (60-70) W, and oxygen gas atmosphere;
[0061] S015. Casting the prepared prepolymer solution on the sample obtained in S014, heating and curing, and peeling it off from the glass slide;
[0062] The prepolymer solution can be selected from thermoplastic polyurethane (TPU), polystyrene-butadiene-polystyrene (SBS), and polydimethylsiloxane (PDMS), and PDMS is preferred.
[0063] S02. Preparation of composite conductive film 4, such as Figure 3 As shown:
[0064] S021. Prepare a one-dimensional nano-conductive solution dispersed in anhydrous ethanol, take the filter membrane and place it on a vacuum filter to obtain a one-dimensional nano-conductive film;
[0065] The one-dimensional nano conductive solution can be selected from a silver nanowire solution, a gold nanowire solution, and a carbon nanotube solution, preferably a silver nanowire solution, and the concentration of the one-dimensional nano conductive solution dispersed in anhydrous ethanol is (20-50) wt%;
[0066] S022. Casting the prepolymer solution on the filter membrane, heating and curing, and peeling it off from the filter membrane;
[0067] S023. Wrap three turns of conductive silver wire around the two ends of the one-dimensional conductive film side of the sample obtained in S022 and fix them with conductive silver glue;
[0068] S024. Casting a viscous solution on the one-dimensional nano-conductive film side, and obtaining a conductive layer 41 after drying;
[0069] The viscous solution can be selected from one of PDA solution, PEI solution and PVA solution, preferably PDA solution;
[0070] S025. S024 is hydrophilized, a two-dimensional conductive solution is added dropwise, and the mixture is heated and dried;
[0071] The two-dimensional conductive solution can be selected from one of graphene oxide solution, MXene solution, tungsten disulfide and molybdenum disulfide, preferably MXene;
[0072] S026. Casting a prepolymer solution to encapsulate and connect the photonic crystal layer to the photonic crystal layer 2;
[0073] The strain visualized ultra-sensitive bionic skin sensor of the present invention requires that the composite conductive film 4 be half-embedded between PDMS, and is realized by vacuum filtering the first layer of one-dimensional nano-conductive film, and then dripping the second layer of two-dimensional conductive film after transfer. Therefore, the first layer of nano-conductive film is embedded in PDMS to stably maintain the conductive path, and the second layer of two-dimensional conductive film is used to increase sensitivity.
[0074] Example 1
[0075] PS nanoparticles were mixed with anhydrous ethanol to obtain a 2% PS nanoparticle solution. 1 ml was measured with a rubber-tipped dropper and slowly dripped onto the surface of deionized water. 500 μl of SDS solution was dripped onto the surface of deionized water. A 30×30 mm clean glass slide was placed in a plasma cleaner and treated for 80 seconds at a pressure of 70 Pa and an oxygen atmosphere. The two-dimensional photonic crystal was removed using the glass slide, dried, and placed in a plasma cleaner for 120 seconds. The PDMS precursor and crosslinker were mixed in a weight ratio of 10:1 and placed in a vacuum box for 40 minutes to remove bubbles. The obtained prepolymer solution was cast on the surface of the two-dimensional photonic crystal, placed on a hot plate at 80°C for 1 hour for curing, and peeled off from the glass substrate after cooling.
[0076] The silver nanowire solution was ultrasonically mixed with anhydrous ethanol to obtain a 30wt% silver nanowire solution. A layer of PTFE filter membrane with a pore size of 0.22μm was placed in a vacuum filter. The mixed silver nanowire solution was vacuum filtered to obtain a layer of silver nanowire film. Three turns of conductive silver wire were wrapped around the two ends of the silver nanowire film and fixed with conductive silver glue. 50μl of PDA solution was dripped on the silver nanofilm, dried and placed in a plasma cleaner, and treated for 30s at a pressure of 70Pa and an oxygen atmosphere. 100μl of MXene solution was dripped on the viscous layer and heated to dry. The PDMS prepolymer solution was cast on the MXene film, placed on a hot plate at 80°C for 10min, connected to the photonic crystal layer, and continued to heat until solidified.
[0077] Example 2
[0078] PS nanoparticles were mixed with anhydrous ethanol to obtain a 3% PS nanoparticle solution. 1 ml was measured with a rubber-tipped dropper and slowly dripped onto the surface of deionized water. 800 μl of SDS solution was dripped onto the surface of deionized water. A 30×30 mm clean glass slide was placed in a plasma cleaner and treated for 80 seconds at a pressure of 70 Pa and an oxygen atmosphere. The two-dimensional photonic crystal was removed using the glass slide, dried, and placed in a plasma cleaner for 240 seconds. The PDMS precursor and crosslinker were mixed in a weight ratio of 10:1 and placed in a vacuum box for 40 minutes to remove bubbles. The obtained prepolymer solution was cast on the surface of the two-dimensional photonic crystal, placed on a hot plate at 80°C for 1 hour for curing, and peeled off from the glass substrate after cooling.
[0079] The silver nanowire solution was ultrasonically mixed with anhydrous ethanol to obtain a 30wt% silver nanowire solution. A layer of PTFE filter membrane with a pore size of 0.22μm was placed in a vacuum filter. The mixed silver nanowire solution was vacuum filtered to obtain a layer of silver nanowire film. Three turns of conductive silver wire were wrapped around the two ends of the silver nanowire film and fixed with conductive silver glue. 80μl of PDA solution was dripped on the silver nanofilm, dried and placed in a plasma cleaner, and treated for 50s under a pressure of 70Pa and an oxygen atmosphere. 150μl of MXene solution was dripped on the viscous layer and heated to dry. The PDMS prepolymer solution was cast on the MXene film, placed on a hot plate at 80°C for 10min, connected to the photonic crystal layer, and continued to heat until solidified.
[0080] Comparative Example 1
[0081] PS nanoparticles were mixed with anhydrous ethanol to obtain a 2% PS nanoparticle solution. 1 ml was measured with a rubber-tipped dropper and slowly dripped onto the surface of deionized water. 500 μl of SDS solution was dripped onto the surface of deionized water. A 30×30 mm clean glass slide was placed in a plasma cleaner and treated for 80 seconds at a pressure of 70 Pa and an oxygen atmosphere. The two-dimensional photonic crystal was removed using the glass slide, dried, and placed in a plasma cleaner for 120 seconds. The PDMS precursor and crosslinker were mixed in a weight ratio of 10:1 and placed in a vacuum box for 40 minutes to remove bubbles. The obtained prepolymer solution was cast on the surface of the two-dimensional photonic crystal, placed on a hot plate at 80°C for 1 hour for curing, and peeled off from the glass substrate after cooling.
[0082] The silver nanowire solution was ultrasonically mixed with anhydrous ethanol to obtain a 30wt% silver nanowire solution. A layer of PTFE filter membrane with a pore size of 0.22μm was placed in a vacuum filter. The mixed silver nanowire solution was vacuum filtered to obtain a layer of silver nanowire film. Three turns of conductive silver wire were wrapped around the two ends of the silver nanowire film and fixed with conductive silver glue. It was placed in a plasma cleaner and treated for 30s under a pressure of 70Pa and an oxygen atmosphere. 100μl of MXene solution was added dropwise to the viscous layer and heated to dry. The PDMS prepolymer solution was cast on the MXene film, placed on a hot plate at 80°C for 10 minutes, connected to the photonic crystal layer, and continued to heat until solidified.
[0083] like Fig.13 As shown, the relative change of the peak value and the change of the peak value average value of the samples of this comparative example and Example 1 during the stretching-releasing cycle test, the strain is 10%, indicating that the stability of the sensor is significantly improved by PDA modification.
[0084] Comparative Example 2
[0085] PS nanoparticles were mixed with anhydrous ethanol to obtain a 2.5% PS nanoparticle solution. 1 ml was measured with a rubber-tipped dropper and slowly dripped onto the surface of deionized water. 600 μl of SDS solution was dripped onto the surface of deionized water. A 30×30 mm clean glass slide was placed in a plasma cleaner and treated for 80 seconds at a pressure of 70 Pa and an oxygen atmosphere. The two-dimensional photonic crystal was fished out using the glass slide, dried, and placed in a plasma cleaner for 360 seconds. The PDMS precursor and crosslinker were mixed in a weight ratio of 10:1 and placed in a vacuum box for 40 minutes to remove bubbles. The obtained prepolymer solution was cast on the surface of the two-dimensional photonic crystal, placed on a hot plate at 80°C for 1 hour for curing, and peeled off from the glass substrate after cooling.
[0086] The silver nanowire solution was ultrasonically mixed with anhydrous ethanol to obtain a 30wt% silver nanowire solution. A layer of PTFE filter membrane with a pore size of 0.22μm was placed in a vacuum filter. The mixed silver nanowire solution was vacuum filtered to obtain a layer of silver nanowire film. Three turns of conductive silver wire were wrapped around the two ends of the silver nanowire film and fixed with conductive silver glue. 100μl of MXene solution was dropped on the sticky layer and heated to dry. The PDMS prepolymer solution was cast on the MXene film, placed on a hot plate at 80℃ for 10min, connected to the photonic crystal layer, and continued to heat until solidified.
[0087] like Fig.14 As shown, it is a comparison diagram of the relative resistance change of the samples of this comparative example and Example 1 under increasing strain. The sample after plasma treatment has higher sensitivity.
[0088] Example 3
[0089] Optical signal test
[0090] In this experimental example, a reflection peak test platform was built by using a spectrometer and an optical fiber. The results are as follows: Fig.15 As shown, within the stretching range of -15%-70%, the structural color shows a transition from blue-purple to red, which shows that the present invention can achieve color changes in the full spectrum of near-visible light within a wide sensing range.
[0091] Example 4
[0092] Electrical signal test
[0093] In this experimental example, an electric displacement platform was built by using a rotating motor and a displacement platform, and a digital source meter was connected to monitor the resistance change of the sensor in real time. The samples prepared in Example 1-2 were subjected to a stretch-release cycle resistance test. The results are as follows: Fig.16 As shown, the resistance change is very stable during 8000 stretching-releasing cycles, which shows that the present invention still has high stability under long-term use.
[0094] Example 5
[0095] Human motion signal monitoring
[0096] The sensor device was fixed to the wrist, throat and face of the subject using transparent tape, and the conductive silver wire of the device was connected to the digital source meter to monitor the human physiological motion signal in real time. The test results are as follows: Fig.17 shown.
[0097] The above description is only by way of illustration of certain exemplary embodiments of the present invention. It is undoubted that those skilled in the art can modify the described embodiments in various ways without departing from the spirit and scope of the present invention. Therefore, the above drawings and descriptions are illustrative in nature and should not be construed as limiting the scope of protection of the claims of the present invention.
Claims
1. An ultra-sensitive bionic skin sensor with strain visualization, characterized in that: It comprises an upper elastic matrix (1), a micro-convex photonic crystal layer (2) arranged on the upper elastic matrix (1), a lower elastic matrix (3), and a composite conductive film (4) arranged in the lower elastic matrix (3); The micro-convex photonic crystal layer (2) is used to simulate the chameleon skin and judge the strain degree through the change of structural color to achieve visual sensing; The photonic crystal is formed by the periodic arrangement of nanoparticles. The micro-convex photonic crystal layer (2) refers to the nanoparticle array embedded in the upper elastic matrix (1) with part of the nanoparticle array exposed on the surface, forming a periodic convex structure. The micro-convex photonic crystal layer (2) produces a high refractive index contrast with the air, and under tensile strain, due to the mismatch between the modulus of the nanoparticles and the elastic matrix, a sinusoidal submicron structure is formed, which acts as a diffraction grating to enhance the two-dimensional Bragg diffraction. The simultaneous action of the two significantly improves the brightness of the structural color. The composite conductive film (4) is used to simulate the slit sensor of spider legs and the elastic fiber of human skin, and achieves high sensitivity through the resistance change of the simulated slit structure during the stretching process, while the simulated elastic fiber structure maintains a high stretching rate; The composite conductive film (4) comprises a conducting layer (41), a connecting layer (42) and a sensitizing layer (43), wherein the conducting layer (41) is composed of a one-dimensional nanomaterial, the connecting layer (42) is composed of an adhesive coating, and the sensitizing layer (43) is composed of a brittle two-dimensional conductive material; The sensitization layer (43) in the composite conductive film (4) is used to simulate the slit sensor of the spider's leg to achieve ultra-high sensitivity, the connection layer (42) is used to enhance the interface adhesion and improve the stability and reliability of the conductive network, and the conduction layer (41) is used to simulate the elastic fibers in human skin to achieve high stretchability.
2. The ultra-sensitive bionic skin sensor with strain visualization according to claim 1, characterized in that: When the sensor is subjected to a slight deformation, the conductive layer (41) in the composite conductive film (4) will produce micrometer-sized cracks, causing the resistance to change sharply, thereby achieving ultra-high sensitivity; when the sensor is subjected to a larger deformation, the cracks will further expand, and the connecting layer (42) will dominate the connection of the conductive path, thereby maintaining the conductivity while enabling the sensor to achieve high elasticity and high elongation.
3. The ultra-sensitive bionic skin sensor with strain visualization according to claim 1, characterized in that: The one-dimensional nanomaterial is selected from any one of AgNWs, AuNWs, and carbon nanotubes; the adhesive coating is selected from any one of polyvinyl alcohol, polyvinylamine, and polydopamine; and the brittle two-dimensional conductive material is selected from any one of MXene, graphene, and molybdenum disulfide.
4. The ultra-sensitive bionic skin sensor with strain visualization according to claim 1, characterized in that: The sensor's electrical signal detection range is 0-80%, the electrical signal sensing sensitivity GF>10, the optical signal detection range is -30-300%, and the optical signal sensing sensitivity is>0.5nm / %.
5. The method for preparing the ultra-sensitive bionic skin sensor with strain visualization according to any one of claims 1 to 4, characterized in that: The following steps are involved: S01. Preparation of micro-convex photonic crystal layer (2): uniformly dispersing a photonic crystal colloidal solution on the surface of deionized water to form a two-dimensional photonic crystal; forming a close-packed structure of the two-dimensional photonic crystal through the surface tension ladder effect; transferring the colloidal nanoparticles to a hydrophilic glass slide and adjusting the gap between them to obtain a non-close-packed structure; adding a polymer solution and curing the solution, and then peeling it off from the glass slide. Since the elastic matrix after curing is still sticky, a part of it will remain on the glass slide during peeling, thereby obtaining a micro-convex structure photonic crystal layer; S02. Preparation of composite conductive film (4): vacuum filtration of the one-dimensional nano-conductive solution, drying to obtain a conductive film; adding a polymer solution dropwise and curing and peeling off; The surface of the conductive film is modified with viscosity to improve the connectivity between the conductive networks; a two-dimensional conductive solution is dripped and dried; a polymer solution is dripped to solidify and encapsulate; S03. The two-dimensional photonic crystal is embedded in the upper elastic matrix (1), and the composite conductive film (4) is semi-embedded in the lower elastic matrix (3), so as to obtain an ultra-sensitive bionic skin sensor with strain visualization.
6. Application of the strain-visualized ultra-sensitive bionic skin sensor according to any one of claims 1 to 4, characterized in that: Ultra-sensitive bionic skin sensors with strain visualization are used in wearable electronics, medical devices, and intelligent robots.
Citation Information
Patent Citations
Stretchable adhesive conductive structure color hydrogel film and preparation method thereof
CN111393708A
Bionic hypersensitive strain sensor with visual effect and preparation method thereof
CN111307107A
Stretchable photonic crystal strain sensor with red shift mechanical color change response
CN117664008A